2014
DOI: 10.1007/s00401-014-1296-9
|View full text |Cite
|
Sign up to set email alerts
|

Pyroglutamylated amyloid-β is associated with hyperphosphorylated tau and severity of Alzheimer’s disease

Abstract: Pyroglutamylated amyloid-β (pE(3)-Aβ) has been suggested to play a major role in Alzheimer's disease (AD) pathogenesis as amyloid-β (Aβ) oligomers containing pE(3)-Aβ might initiate tau-dependent cytotoxicity. We aimed to further elucidate the associations among pE(3)-Aβ, full-length Aβ and hyperphosphorylated tau (HP-τ) in human brain tissue. We examined 41 post mortem brains of both AD (n = 18) and controls. Sections from frontal and entorhinal cortices were stained with pE(3)-Aβ, HP-τ and full-length Aβ ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 37 publications
5
46
0
Order By: Relevance
“…Furthermore, pyro-glu Aβ only weakly correlated with individual Braak stages and failed to correlate with any measure of cognition. This is largely at odds with previous reports of disease specificity [52] and toxicity [61], although in agreement with previous work where a correlation was established between levels of pyro-glu-modified Aβ and tau phosphorylation [52]. …”
Section: Discussionsupporting
confidence: 77%
“…Furthermore, pyro-glu Aβ only weakly correlated with individual Braak stages and failed to correlate with any measure of cognition. This is largely at odds with previous reports of disease specificity [52] and toxicity [61], although in agreement with previous work where a correlation was established between levels of pyro-glu-modified Aβ and tau phosphorylation [52]. …”
Section: Discussionsupporting
confidence: 77%
“…The predominance of pE-A␤ in the central core of plaques suggests an early involvement in amyloid deposition in the AD brain (52), whereas correlation between pE-A␤ and a decline in Mini Mental State Examination scores implicate pE-A␤ cytotoxicity in AD neurodegeneration (53,54). In parallel, markers of oxidative stress are among the earliest detectable pathological changes in transgenic AD mouse models (55) and the human AD brain (36,56,57), with numerous lines of evidence implicating A␤ as a central contributor to oxidative stress in AD (58,59).…”
Section: Discussionmentioning
confidence: 99%
“…Also, it has been demonstrated that pGlu-3 Aβ may act as a nidus for template-induced protein misfolding and oligomerization, both with itself and with free Aβ1-42 to generate cytotoxic low-molecular weight oligomers (Nussbaum et al, 2012). Recently, QC expression and pGlu-3 Aβ accumulation in human AD brain has been shown to correlate with cognitive decline (Morawski et al, 2014, Pivtoraiko et al, 2014) and tau pathology (Mandler et al, 2014). Thus, cumulating evidence from human post-mortem tissue and mouse models suggest pGlu-modified Aβ as a species causally involved in AD progression and cognitive decline (Rijal Upadhaya et al, 2014, Saido et al, 1995).…”
Section: Introductionmentioning
confidence: 99%